ANALISIS SISTEM INFORMASI AKUNTANSI PEMBIAYAAN SYARI’AH PADA BAITUL QIRADH SURYA MADINAH BANDA ACEH - Irmawati, Irmawati (Fakultas Ekonomi Universitas Muhammadiyah Aceh, 2011)
Irmawati (Dosen Tetap Fakultas Ekonomi Universitas Muhammadiyah Aceh) Erlindawati (Alumni Mahasiswa FE Unmuha) ABSTRACT Objective of this research is to know accounting information system costing to Syari’ah Baitul Qiradh Surya Madinah Banda Aceh. Collecting data doing by field observation interview and literature study. Data analysis use descriptive qualitative that data doing evaluation and analysis based on theory. Objective is to make resume and give advise on accounting information system costing to Syari’ah Baitul Qiradh Surya Madinah Banda Aceh. Keyword : Accounting System Information, Costing